2018
DOI: 10.1155/2018/9705728
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Bladder and Ureter Hernia Permagna: Definition of a Rare Clinical Entity and Case Report

Abstract: Background Inguinoscrotal herniation of the bladder is a rare clinical entity, with a frequency between 0.5% and 4% of all inguinal hernias. The bladder can partially or entirely herniate into the inguinal canal; when the whole bladder and ureters migrate into the scrotum, it may cause urinary disorders. Case Presentation A 62-year-old male patient presented with urinary disorders and right-sided inguinoscrotal hernia. Under clinical suspicion of bladder involvement in the inguinal canal, abdominal and pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
18
1
1
Order By: Relevance
“…In the present case, there was no such history, and that makes it extremely unique. There are case reports of herniation of the ureter along with the urinary bladder [6]; however, in this case, it was an isolated herniation of the ureter with hydroureteronephrosis without a visible calculus. Two types of ureteral herniations have been described: paraperitoneal and extraperitoneal [7,8].…”
Section: Discussionmentioning
confidence: 72%
“…In the present case, there was no such history, and that makes it extremely unique. There are case reports of herniation of the ureter along with the urinary bladder [6]; however, in this case, it was an isolated herniation of the ureter with hydroureteronephrosis without a visible calculus. Two types of ureteral herniations have been described: paraperitoneal and extraperitoneal [7,8].…”
Section: Discussionmentioning
confidence: 72%
“…There are few reports of upper tract obstruction secondary to inguinoscrotal hernia in the literature, and all these cases are unilateral. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Possible imaging modalities to diagnose bladder herniation include non-contrast CT, CT urogram or ultrasound of the urinary tract and scrotum, 1 however it has been suggested that all patients receive a CT scan at some point due to a weak association with urinary tract malignancy. 3 …”
Section: Introductionmentioning
confidence: 99%
“…При увеличении внутрипузырного давления мочевой пузырь может выбухать в паховый канал. Это встречается в 0,5-4% всех паховых грыж [7]. Описано дивертикулярное выбухание пузыря в бедренный канал [8].…”
Section: резюмеunclassified